'Seeing the Wood for the Trees': Revisiting the Consistency of Australia's Illegal Logging Act with the Law of the World Trade Organization. (8th April 2021) - Gascoigne, Catherine E
Abstract: In the absence of coordinated multilateral action, many countries seek to address environmental harm occurring in foreign jurisdictions by introducing measures that regulate the importation of certain products. In Australia, the Illegal Logging Prohibition Act 2012 (Cth) and the Illegal Logging Prohibition Regulation 2012 (Cth) prohibit the import of timber that has been harvested in a manner that is contrary to the laws of the harvesting country. One unsettled question is whether the measure is inconsistent with the law of the World Trade Organization. This article considers this question ahead of the Commonwealth Government's 10-year review of the Measure. To this end, the article examines the consistency of the Act with the General Agreement on Tariffs and Trade and the Agreement on Technical Barriers to Trade. The findings of the article are relevant to Australia and to other countries that design and implement measures to regulate the importation of products for environmental objectives.